Water relations and yield characteristics of mungbean as influenced by foliar application of gibberellic acid (GA3) - Islam, Mohammad Sohidul; Hasan, Md. Kamrul; Islam, Md. Rafiqul; Chowdhury, Md. Kaium; Pramanik, Moaz Hosen; Iqbal, Muhammad Aamir; Rajendran, Karthika; Iqbal, Rashid; Soufan, Walid; Kamran, Muhammad; Liyun, Liu; El Sabagh, Ayman (Frontiers in Ecology and Evolution, 2023)
Optimizing the dose and frequency of application of growth regulators such as gibberellic acid (GA3) may play an important role in ensuring food security under changing climate scenarios by multiplying economic yield of food crops such as mungbean. A trial was conducted to evaluate the growth promoting effect of foliage applied gibberellic acid (GA3) at various spraying frequencies for mungbean crop. Water relations, yield contributing characteristics and mungbean grain yield were among the variables investigated. The trial included four gibberellic acid levels (0, 100, 200 and 300 ppm) and two application frequencies (only one application at 30 days after sowing, and two applications at 30 and 40 days after sowing). The findings revealed that GA3 significantly improved the water relations, morphological and yield attributes of mungbean (200 ppm applied twice at pre-flowering and post-flowering stages). It produced the highest relative water content in the stem (85.52), water retention capacity in the stem (17.24), and water uptake capacity in the stem and leaf (2.35). Furthermore, the same treatment combination resulted in plant height (50.04 cm), pods per plant (11.07), pod length (6.62 cm), grains per pod (11.00), 100 grains weight (3.78g), grain yield per plant (4.57 g) and a minimum water saturation deficit.Thus, GA3 foliage application at 200 ppm at 30 and 60 DAS has the potential to stimulate growth and increase yield characteristics of mungbean, potentially yielding much more grain than the control treatment. However, additional in-depth field trials with various doses of GA3 sprayed at a higher frequency may be required before recommending GA3 for general adoption by mungbean growers.